Analysis of rotational deformity correction by lateral lumbar interbody fusion with two-staged anterior-posterior combined corrective fusion surgery for adult degenerative kyphoscoliosis. Issue 37 (16th September 2022) - Abe, Tetsutaro; Miyazaki, Masashi; Kanezaki, Shozo; Hirakawa, Masashi; Iwasaki, Tatsuya; Tsumura, Hiroshi
Abstract : The present study is retrospective analysis of consecutively collected data. Lateral lumber interbody fusion (LLIF) is widely used in cases of adult spinal deformities. However, the corrective effects of LLIF cage insertion on the vertebral rotation deformity in the axial plane and the individual effects of LLIF and direct vertebral rotation (DVR) on rotational correction are unclear. To individually examine the corrective effects of LLIF and posterior corrective fusion surgery with direct DVR on vertebral rotation deformities in adult degenerative kyphoscoliosis. We analyzed 21 patients (5 males and 16 females) who underwent two-staged anterior-posterior combined corrective fusion surgery for adult degenerative kyphoscoliosis. Surgical time, blood loss, facet joint osteoarthritis (OA) grade, disc degeneration, cage height, vertebral rotational angle, and various X-ray parameters were investigated as evaluation items. The X-ray parameters showed significant postoperative improvements. The mean vertebral rotation angle was 6.4° ± 5.2° preoperatively, 3.5° ± 3.3° after LLIF ( P  = .014, vs preoperative), and 1.6° ± 1.7° after posterior corrective fusion surgery with DVR ( P  = .011, vs preoperative). Correlation analysis between the vertebral rotation angle and various measured values revealed that the vertebral rotation angle after LLIF was correlated with the cage height ( r  = −0.46, P  = .032). The vertebral rotation angle after DVR was correlated with the facet joint OA grade ( r  = −0.49, P  = .018) and the wedge angle after posterior corrective fusion surgery with DVR ( R  = 0.57, P  = .006). We conclude that the effects of rotational deformity correction with LLIF cage insertion and additional posterior corrective fixation with DVR can be useful for correcting vertebral rotation deformities.